2012
DOI: 10.3390/rs4040830
|View full text |Cite
|
Sign up to set email alerts
|

LiDAR Sampling Density for Forest Resource Inventories in Ontario, Canada

Abstract: Over the past two decades there has been an abundance of research demonstrating the utility of airborne light detection and ranging (LiDAR) for predicting forest biophysical/inventory variables at the plot and stand levels. However, to date there has been little effort to develop a set of protocols for data acquisition and processing that would move governments or the forest industry towards cost-effective implementation of this technology for strategic and tactical (i.e., operational) forest resource inventor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
92
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 37 publications
6
92
3
4
Order By: Relevance
“…The results of the stand height variables models H m and H 0 (R 2 adj = 0.95, RMSE = 0.385 m and R 2 adj = 0.91, RMSE = 0.506 m, respectively) are similar, in terms of R 2 of that achieved by Treitz et al (2010), and better than those provided by Gobakken and Naesset (2007) in Norway Spruce an Scots pine in Norway and González-Ferreiro et al (2012); although the goodness-of-fit statistics are lower than those achieved by Stephens et al (2008).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The results of the stand height variables models H m and H 0 (R 2 adj = 0.95, RMSE = 0.385 m and R 2 adj = 0.91, RMSE = 0.506 m, respectively) are similar, in terms of R 2 of that achieved by Treitz et al (2010), and better than those provided by Gobakken and Naesset (2007) in Norway Spruce an Scots pine in Norway and González-Ferreiro et al (2012); although the goodness-of-fit statistics are lower than those achieved by Stephens et al (2008).…”
Section: Discussionsupporting
confidence: 56%
“…Something similar happened with the dg model (R 2 adj = 0.96, RMSE = 0.370 cm), which performed much better than those reported by Naesset (2002Naesset ( , 2004 for mean diameter and Gonçalves-Seco et al (2011) for mean and quadratic mean diameter, but in the order of the results obtained by Ruiz et al (2014b). Finally, stand basal area estimates derived from the linear model (R 2 adj = 0.97, RMSE = 1.33 m 2 ha -1 ) was similar to those achieved by Treitz et al (2010) in black spruce forests of Canada, but was even better than those reported by Naesset (2002), Lim et al (2003) for Canadian broadleaf forests, Stephens et al (2008) in radiata pine forests of New Zealand or Gonçalves-Seco et al (2011) and González-Ferreiro et al (2012) in Spain. The high crown diameter of adult P. pinaster trees and AB the regular and homogenous structure of these single-stratified stands could help to obtain good estimates of these parameters related with stand density.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We showed in [34] that, for example, for a grid-cell size of 10 m × 10 m and a point density of 10 pts/m 2 , the derived RFDs match to ~95% with RFDs based on much higher point densities Whether this loss of information is significant or important still depends on the research question and/or the planned application. For example, Wilkes et al [70], Hawbaker et al [71], and Treitz et al [42] pointed out that lower point densities (<5 pts/m 2 ) are sufficient for canopy-structure analysis regarding tactical forest management, but these findings are only valid for canopy-structure descriptors derived on larger scales than the one we used in this study. Hayashi et al [72], in contrast, concluded that in complex forests, low-density ALS data was ineffective in estimating the defined canopy-structure descriptors with sufficient accuracy.…”
Section: Discussioncontrasting
confidence: 48%
“…Most canopy-structure components, however, have inherent spatial scales and the choice of the spatial scale should be made considering the investigated structural component [40,41]. Nevertheless, an acceptable compromise often needs to be found between the technical capabilities of ALS and user needs, such as the application domain or cost-benefit considerations [42,43]. In this study, ABAs represented in regularly spaced grids were used, allowing flexible analysis in terms of spatial scales and cross-scale comparisons (e.g., testing reproducible up-and down-scaling methods).…”
Section: Introductionmentioning
confidence: 99%